The Effect of Preheat and Post Weld Heat Treatment On Welding ASTM A 516 Grade 60 Material On Destructive Test Values - Rizqi Jati Alwani; Arif Fadillah (Institut Teknologi Sepuluh Nopember, 2023)
In the construction of independent tanks (spherical) must be related to welding. Welding itself has a very important role in the process of connecting steel plates. The aims of the research is to determine the effect of the presence or absence of preheat and PWHT on welding and uses ASTM A 516 grade 60 steel material, where the material is commonly used for the construction of tanks or pressure vessels. The steel material is welded by the SMAW (shield metal arc welding) welding process with several different welding variables, one of which is given the preheat and post weld heat treatment (PWHT) variables and the other is not given these variables. Then the material will be tested mechanically, such as bending test, tensile test, and impact test under low temperature conditions (-20oC). The method used in this research is experimental. From the results of the tests will be known the value of tensile strength and energy absorbed. In the welding test specimen with preheat and PWHT variables, an opening of 1.68 mm was obtained, with an average tensile strength value of 523 N/mm2, and an average energy value of 205.15 J. While in the specimen without preheat and PWHT variables, the opening was obtained. of 1.21 mm, with an average tensile strength value of 473.5 N/mm2, and an average energy value of 46.7 J.